A feasibility study of a leaky waveguide aptasensor for thrombin. Issue 20 (13th September 2019) - Alamrani, Nasser A.; Greenway, Gillian M.; Pamme, Nicole; Goddard, Nicholas J.; Gupta, Ruchi
Abstract : This proof-of-principle study demonstrates the feasibility of a leaky waveguide (LW) aptasensor, where aptamers were immobilised in a mesoporous chitosan waveguiding film for the detection of thrombin. Abstract : This proof-of-principle study demonstrates the feasibility of a leaky waveguide (LW) aptasensor, where aptamers were immobilised in a mesoporous chitosan waveguiding film for the detection of thrombin. This work has demonstrated that aptamers immobilised in hydrogels retain their affinity and selectivity towards their target and thus can be used as bioreceptors. The use of antibodies as bioreceptors for sensing thrombin is not viable because it is a serine protease, which will cleave the antibodies. Currently used assays based on clotting time and chromogenic/fluorogenic substrates have limited potential for thrombin measurement in whole blood. Using the initial binding rate over the first 5 min, the limit of detection of our LW aptasensor for thrombin was ∼22 nM. The sensor was tested with spiked serum samples, giving a reading of 46.1 ± 4.6 nM for a sample containing 50 nM thrombin. Our proposed sensor combines the robustness and low cost of aptamers as molecular recognition elements with the simple fabrication process of the chitosan-based leaky waveguide, making LW aptasensors highly attractive for applications in point-of-care diagnostics and healthcare monitoring.